1991
DOI: 10.1002/jnr.490300126
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytoskeletal, focal adhesion, and cell adhesion proteins in growth cone particles isolated from developing chick brain

Abstract: Growth cones are intimately involved in determining the direction and extent of neurite elongation during development. They are able to monitor their environment and respond to it by undergoing directed motility. We have isolated a fraction enriched in growth cone particles from embryonic chick brain. Assayed by immunoblots, this fraction is enriched in GAP-43, and contains the cytoskeletal proteins actin, myosin II, neurofilament protein, tubulin, kinesin, and dynamin. All of the major components of focal adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The number of cytoskeletal and signaling components found at adhesion sites now exceeds 20, and dynamin is a newly confirmed addition to this complex, exhibiting several interactions with focal adhesion components. Recent findings now extend a seminal observation by Cypher and Letourneau (Cypher and Letourneau, 1991), who observed that dynamin is enriched at adhesion sites in growth cones from embryonic chick brain.…”
Section: Dynamics At the Cell Basesupporting
confidence: 82%
“…The number of cytoskeletal and signaling components found at adhesion sites now exceeds 20, and dynamin is a newly confirmed addition to this complex, exhibiting several interactions with focal adhesion components. Recent findings now extend a seminal observation by Cypher and Letourneau (Cypher and Letourneau, 1991), who observed that dynamin is enriched at adhesion sites in growth cones from embryonic chick brain.…”
Section: Dynamics At the Cell Basesupporting
confidence: 82%
“…Focal adhesions are elongated in morphology and reside in both central and peripheral regions of the cell, and are generally found at the ends of actin filament bundles. Analogous adhesion structures have been observed in vivo in endothelial cells (Kano et al 1996), skeletal muscle myotendinous junctions (Turner et al 1991), and neuronal growth cones (Cypher and Letourneau 1991), and highly elongated adhesions have also been reported in vivo (Cukierman et al 2001).…”
Section: Focal Adhesionssupporting
confidence: 60%
“…To examine NOX-dependent ROS production in neuronal growth cones, we utilized freshly isolated growth cone particle preparations (GCPs) obtained from chick E10 forebrain neurons, which are capable of showing complex responses to extrinsic stimuli [3739]. As shown in Figure 4(a), addition of 100 ng/mL TNF α to laminin-adherent GCPs resulted in MAP kinase and JNK activation, which was corroborated in cultured forebrain neurons.…”
Section: Resultsmentioning
confidence: 99%